Kecemasan Berbahasa Arab ‘Āmiyah Saudi Mahasiswa Program Studi Manajemen Haji dan Umrah dalam Konteks Diglosia - Zainurrakhmah, Zainurrakhmah; Wati, Wiwit Rahma (Aphorisme: Journal of Arabic Language, Literature, and Education, 2026)
This study aims to describe the foreign language anxiety (FLA) profile of students in the Hajj and Umrah Management (MHU) program at UIN Walisongo Semarang and to identify the factors underlying their anxiety in using Saudi Arabic colloquial (ʿāmiyah) within the context of Arabic diglossia. Although MHU students are expected to communicate directly with native Arabic speakers in professional settings, Arabic instruction in higher education has predominantly focused on formal Arabic (fuṣḥā), leaving students both linguistically and psychologically underprepared for authentic ʿāmiyah interaction. This qualitative case study examined the MHU program at UIN Walisongo Semarang as the unit of analysis, using data from 87 students who had completed the Saudi Arabian ʿāmiyah course as the primary evidence. Data were collected through two techniques: a questionnaire based on the Foreign Language Classroom Anxiety Scale (FLCAS) comprising 33 items on a five-point Likert scale across three dimensions, namely communication apprehension (CA), fear of negative evaluation (FNE), and test anxiety (TA), and an open-ended questionnaire with three narrative questions to explore the underlying causes of anxiety. Scalar data were analyzed descriptively by calculating means per item and dimension, while narrative data were analyzed using content analysis with open coding, category grouping, and thematic synthesis. Results indicate a moderate overall anxiety level (M = 3.49), with FNE as the highest dimension (3.52), followed by CA (3.50) and TA (3.45). The proximity of scores across dimensions suggests that affective barriers operate across all aspects of language use rather than in isolation. Content analysis identified six contributing factors in two intersecting layers: structural-linguistic, comprising ʿāmiyah vocabulary deficit and fuṣḥā–ʿāmiyah diglossic interference; and situational-pedagogical, comprising limited communicative practice, psychological unpreparedness, evaluation pressure, and social evaluation anxiety. These findings imply the need for more communicative, contextual, and diglossia-sensitive curriculum development in Saudi Arabian ʿāmiyah instruction.